Architectural design criteria and their application in multi-storey residential buildings in the Klang Valley / Yong Kuan - Yong, Kuan (2013)
This research focuses on certain design issues in architectural practice that have been influenced by architects, clients and the market. In practice, the design and production of buildings work in a social context comprising the profession, clients, users, architects, consultants, and contractors. The work dynamics of client-architect interactions in the market influence the conception of architectural design. The resultant design affects the quality of buildings which in turn has life-long effects on people and the environment. This research began with the question of why certain multi-storey residential buildings lack architectural design quality. The research aims to determine architectural design criteria, apply these criteria to establish the relationships between design quality and market price, and test a hypothesis i.e. architectural design quality decreases as market price decreases. It validates two hypotheses i.e. clients are more dominant than architects in making design decisions, and there is a lack of congruence of the design quality in buildings between the users to whom the architects are ethically responsible and the clients to whom the architects are accountable. A theoretical framework was developed, which then guided a mixed methods research including case studies and surveys. These methods underline non-equivalent dependable variables design, pattern-matching, replication, descriptive and inferential statistics. The determination of design criteria utilised from literature review and survey. For establishing the bivariate relationships involved case studies of eight developers, case studies of seven architectural firms, and surveys of low, medium and high cost residential buildings. The survey results analysed with t-test (p≤0.05) on criteria determination established a majority opinion of agreement (test-results>4"agree") on six design criteria, except for Feng Shui which scored 49.50% agree, 36.80% neutral and 13.7% disagree. These results established the first ever set of architectural design criteria for multi-storey residential buildings in Malaysia. The results of case studies and surveys generally established positive and significant correlation (p≤0.05), linear and causal regression, case replication, observed and predicted pattern-matching and positive hypothesis testing. The findings confirm the three hypotheses to be true. The findings of this research contribute to the body of knowledge in architecture, the profession, and practices.